PENGUATAN PENDIDIKAN KARAKTER RELIGIUS SISWA KELAS 5 MELALUI BUDAYA SEKOLAH DI SDN POGAR II BANGIL - Kharisma Noor Afni Noviana; Muhlasin Amrulloh (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2023)
This study aims to find out: (1) to what extent does the school as a formal educational institution carry out strengthening the religious character education of fifth-grade students?, (2) what are the problems and efforts to resolve the implementation of strengthening religious character education for fifth-grade students, and (3) the results of strengthening religious character education for fifth-grade students at SDN Pogar II Bangil. This study uses a qualitative approach. This research was conducted at SDN Pogar II Bangil in the 2022/2023 academic year. The data sources for this research were informants consisting of principals as key informants, class teachers, and grade 5 students. Data collection techniques used interviews, observation, and documentation. Data analysis was carried out in a qualitative descriptive manner. The research results show that: (1) strengthening the religious character education of fifth-grade students through school culture is carried out through understanding, habituation, and exemplary. (2) obstacles to strengthening religious character education for fifth-grade students through school culture: teacher's ability to advise, influence, and motivate students, it is difficult to measure the success of instilling character values, there is no sync between habituation and exemplary character planted in schools with treatment, habituation, and exemplary at home. While the supporting factors: parental commitment, teacher commitment in instilling students' religious character values. (3) the results of strengthening students' religious character education through school culture are: students become pious/pious individuals, students have high moral integrity, and students have good morals.